Beyond Numbers: Beyond Numbers: Exploring Factors Influencing Company Value In Indonesian Consumer Goods (2018-2022) - Ahmad, Darmawel; Nuryaman, Nuryaman (Politeknik Ganesha Medan, 2024)
This study analyzed Indonesian consumer goods' business value determinants (2018-2022) using numerical methods, focusing on the impact of key variables like debt-to-equity ratio, total asset turnover, logarithm of assets, and return on equity. The research investigated the influence of these factors on companies listed on the Indonesian Stock Exchange, revealing significant effects of debt-to-equity ratio and total asset turnover on return on equity and subsequently on price-to-book value. The logarithm of assets directly affected return on equity but had no impact on price-to-book value. Regression analysis, measured by R-Square and Q-Square values, demonstrated the variables' impact on cost-to-book value and return on equity. The study confirmed that financial leverage and asset utilization significantly affect enterprise value, highlighting the importance of effective financial management in optimizing investment returns in Indonesia's consumer goods sector.